Novel Activity of Rhodobacter sphaeroides Spheroidene Monooxygenase CrtA Expressed in Escherichia coli - Lee, Pyung Cheon (American Society for Microbiology (ASM), 2010)
The spheroidene monooxygenase CrtA of Rhodobacter sphaeroides introduces a keto group and/or hydroxy group at the ends of nonnative substrates in Escherichia coli, resulting in the production of novel oxocarotenoids. The heme-containing CrtA is not a P450 enzyme but a new type of oxygenase.